2019
DOI: 10.1016/j.ssmph.2019.100414
|View full text |Cite|
|
Sign up to set email alerts
|

Ecological zone and symptoms of acute respiratory infection among children under five in Ghana: 1993–2014

Abstract: Since 1993, evidence suggest that a significant portion of Ghanaian under-five children have suffered from Acute Respiratory Infection (ARI). This study sought to examine the prevalence of ARI symptoms among under-fives across ecological zones as well as childhood and maternal factors associated with ARI between 1993 and 2014. We used data from Ghana Demographic and Health Surveys (1993–2014). The study sample included women of reproductive age who had under-five children experiencing a cough accompanied with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…Children from rural setup were more prone to develop ARI in the current study which is in line with several earlier studies [12,39,[44][45][46]. The probable justification for the greater ARI symptoms proportion for rural children may be due to lack of access to medical care, low socio-economic standards in rural regions [47] and most risk factors for ARI prevail in rural setup [48].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Children from rural setup were more prone to develop ARI in the current study which is in line with several earlier studies [12,39,[44][45][46]. The probable justification for the greater ARI symptoms proportion for rural children may be due to lack of access to medical care, low socio-economic standards in rural regions [47] and most risk factors for ARI prevail in rural setup [48].…”
Section: Discussionsupporting
confidence: 89%
“…Several factors predispose children under five years of age for ARIs. These factors may be attributed to child factors such as age [11][12][13][14][15] and female sex [16], maternal factors such as lower age [11,13], unemployment [11,13] and lower educational status [16,17] environmental-related factors such as urban residence [17], rural residence [18], wet season [19][20][21] and co-morbid diseases [14,22,23]. There is a paucity of studies regarding the prevalence and associated factors of ARI among hospitalized under-five years children in Ethiopia even though few community-based cross-sectional studies [24][25][26] have been undertaken in to assess the prevalence and associated factors of ARIs among under-five years children.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian ini menggunakan data dari Survei Demografi dan Kesehatan Ghana . Sampel penelitian termasuk wanita dari usia reproduksi yang memiliki anak balita dengan gejala batuk disertai nafas pendek yang cepat dalam dua minggu terakhir sebelum survei dilaksanakan (Seidu, Kwabena, Opoku, Baatiema, & Appiah, 2019).…”
Section: Profesional Health Journalunclassified
“…The majority of factors of ARI occur in rural areas and among children under one year of age (Mirji et al 2014). Several studies showed that Children from rural setups were more prone to develop ARI [ 24 , 25 ]. The probable explanation for the greater ARI symptoms proportion for rural children may be due to lack of access to medical treatment, low socio-economic standards in rural regions [ 26 ].…”
Section: Introductionmentioning
confidence: 99%